Earnings Persistence In Affecting Stock’s Prices Of Malaysia And Indonesia Manufacturing Companies - nuraini rokhmania; Titis Puspitaningrum Dewi Kartika (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The users of financial reports usually use the information of current earnings to predict future earning so that quality earnings are earnings that can reflect the continuity of earning in the future.. This study takes company samples of manufacturing companies, both of which listed in Indonesia’s stock exchange as well as Malaysia’s in the yeas 2014 – 2017 by using regression and intervening analysis. The results of this study are operating cash flow cannot affect the earnings’ persistence in Indonesia but it affect in Malaysia, book tax differences and debt level can affect an earning persistence in Indonesia & Malaysia, earnings persistence could affect stock prices in Indonesia & Malaysia and Operating cash flow cannot affect stock prices with Earning Persistence as intervening variable for manufacturing companies in Indonesia & Malaysia. Research Limitations/implications: Adj R square value is very low and cannot be compared between Indonesia and Malaysia. Practical Implication: the result would be beneficial for researchers who eager to analyse the similar variable against different countries.